Power through: A new concept in the empowerment discourse - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
The concept was published in a peer-reviewed journal in 2019. An improved understanding of the complex relational nature of empowerment can facilitate the ability of Research for Development to develop more accurate measurements of empowerment and develop effective strategies to enhance women's empowerment.